A mechatronic shape display based on auxetic materials - Anthony Steed (Nature Portfolio, 2021)
Though shape-changing devices are promising for future haptic displays, existing designs fail to provide smooth surfaces for the user during tactile exploration. Here, the authors utilize flexible auxetic structures to realize shape displays with smooth surfaces and different Gaussian curvatures.